TERORISME ISLAMIC STATE OF IRAQ AND SYRIA (ISIS) DALAM NOVEL HABĪBĪ DĀ‘ISYĪ KARYA HĀJAR ‘ABDUṢ ṢAMAD: ANALISIS HEGEMONI GRAMSCI - Rumpoko Setyo Jatmiko (Arabic Literature Department, 2019)
The phenomenon of terrorism which is the subject of world discussion today, namely ISIS has attracted an Egyptian writer to be illustrated in a novel entitled Habībī Dā‘isyī. This novel tells the story of the struggle of a woman and her family in facing terror committed by ISIS. Laila was involved in and joined ISIS along with several other Egyptian women. At that time she felt ignored and pressured by her own family. The novel is examined and examined through Gramsci's Hegemony theory related to intellectual-moral leadership and its dominance to find out various acts of terror being excercised, in addition to how to hegemony Egyptian society, which is the setting and character of this novel. The analysis of the novel shows that ISIS is a terrorist organization which inculcates the ideology of 'jihad' to attract public sympathizers. ISIS uses violence in its actions to dominate and cause many casualties. In addition to these two things, there is an important figure, namely the leader who calls himself as khalīfah which compiles everything, therefore ISIS is known throughout the world today. All their committed actions aim to establish ad-Daulah al-Islāmiyyah or Khilāfah Islāmiyyah 'Islamic state', a country that upholds the commands and prohibitions in the Shari'a of Allah SWT.